Pengaruh Kualitas Layanan & Citra Merek Terhadap Loyalitas Pelanggan Melalui Kepuasan Pelanggan di Nagadigit - Evelyna Septiani Hirawan; Siti Nurjanah (UNIVERSITAS KALBIS, 2023)
This study aims to identify the effect of service quality & brand image on customer loyalty through Nagadigit customer satisfaction. This study uses a quantitative method using SPSS. This research technique uses survey research techniques with online questionnaire distribution data collection methods. The sampling technique used was the Slovin technique with 94 respondents. This study uses validity, reliability, classical assumptions and hypotheses. In the hypothesis test, the results of the path analysis test conducted show that the effect of service quality (X1) and brand image (X2) on customer loyalty (Z) through customer satisfaction (Y) has a smaller coefficient when compared to the effect of service quality (X1) and brand image (X2) on customer loyalty (Z) directly, so that customer satisfaction (Y) cannot be an intervening variable between service quality (X1) and brand image (X2) on customer loyalty (Z).